Factors influencing career exploration goal among hospitality and tourism diploma students in private colleges in the Klang Valley, Malaysia - Mohd Hashim, Sabrina (2024)
Hospitality and tourism play an important role in global economic development and creating job opportunities. This has led to the increase in the number of graduates which is an indication on the need for the program to supplement the demand of the workforce in the industry. Despite this phenomena, previous studies have indicated that, the industry fails to attract the right candidates. The career self- management (CSM) model is the underlying theory guiding this study in which focus is on career exploration tasks and job seeking behaviour. This study examines the relationship between career decision selfefficacy, career optimism and outcome expectation towards exploratory goals. A quantitative method through online survey questionnaire was distributed to 14 private colleges in Klang Valley. The unit of analysis for this study are hospitality and tourism diploma students in their final year, from private colleges in Klang Valley. This includes programs under hotel, travel, tourism, hospitality, accommodation, culinary, gastronomy and foodservice. A total of 190 students of diploma in hospitality and tourism students completed the survey. Out of the 190 responses, only 129 responses were accepted for analysis. Findings from all the three predictors (career decision self-efficacy, career optimism and outcome expectation) was found to explain 60.8% of the variance in exploratory goals. Additionally, two predictors (career decision selfefficacy and career optimism) showed a significant influence on exploratory goals with career optimism indicated t-value = 5.351 and p< 0.05, while career decision self-efficacy with t- value = 5.140, p< 0.05. However, Outcome Expectation was found to negatively influence Exploratory Goal. The result indicated (β = -0.181, p = 0.13), thus the hypothesis is not supported. Next, result indicated that career decision self-efficacy explains 53.7% of the variance in career optimism. Finally, career decision self-efficacy explains 35.1% of the variance in outcome expectation. In conclusion, the current study has provided evidence on the strong favourable impact of Career Decision Self-Efficacy and Career Optimism on Exploratory Goal. Whilst the relationship between Career Decision Self-Efficacy and Exploratory Goals was found to be mediated negatively by Outcome Expectations, the mediation analysis has proven that the association between Career Decision Self- Efficacy and Exploratory Goals was shown to be mediated by Career Optimism. Thus, this validates the significance of career optimism in the career exploration process which is an extension to the existing CSM model. The model in this study is anticipated to be the first to examine the career exploration process of hospitality and tourism diploma students of private colleges in Klang Valley. The findings of this study will enable educational institutions and the industry to have a better understanding and identify factors of student’s career decision making which could lead to greater retention of hospitality graduates in the industry